Figure 2 from: Elvebakk A, Bjerke JW (2024) Papaver recircumscribed: A review of neighbouring Papaveraceae genera, including Afropapaver nom. et stat. nov. and Oreomecon, a large, Arctic-Alpine genus. PhytoKeys 248: 105-188. https://doi.org/10.3897/phytokeys.248.121011 - Elvebakk, Arve; Bjerke, Jarle W. (Zenodo, 2024)
Figure 2 World distribution of the genera Cathcartia (grey), Meconopsis (sky blue), Oreomecon (yellow) and Roemeria (red). The total distribution of Oreomecon is divided into eight geographical areas (A–H) both on the map and in the textual treatment. Area E consists of two almost equally large subareas, while area H consists of one main subarea and four much smaller subareas (see arrows). Note also that the total distribution of Cathcartia consists of four different subareas. See Table 1 for the numbers of species and subspecies per genus and for each of the subareas of Oreomecon.